INVESTIGATING THE PROBLEMS OF TEACHING AND LEARNING ENGLISH IN MIDDLE SCHOOLS IN IRAN - Saloumeh Khodabakhshi; Ali Rahimi (English Review: Journal of English Education, 2013)
Abstract: The present research aimed to investigate the problems of teaching and learning English in middle schools in Esfahan, Iran. These problems are associated with the learner, teacher, textbook, syllabus, and language policy. The instrument used was a self-constructed likert scale questionnaire. All the variables had a hand in the problems among which textbook, syllabus and language policy had the most effect. Twenty five problems were distinguished among which some are as follows: students do not consider pair work important; most of the time, most teachersÂ  do not speak in English in the classroom; the textbook does not include CDs or cassettes, does not consists of all the English Skills; the syllabus does not include one or two projects for students apart from the midterm or final test, Language Policy being not completely familiar with the steps of EFL teaching, does not selecting the most qualified and proficient teachers in EFL teaching. It can be concluded that the language policy should take a practical step in reducing the problems by changing the textbooks and providing more teaching aids for the teachers.Keywords: teaching and learning English, problems of teaching and learning English, middle school, Iran